Analisis Penyimpangan Pembiayaan BPRS dan Implikasinya terhadap Kesejahteraan Pelaku UMKM (Studi Kasus Bank Perekonomian Rakyat Syariah Haji Miskin Pandai Sikek) - Rani Junia Salputri; Septria Susanti (ARZUSIN, 2026)
The misuse of financing funds by MSME actors has become a focus in various previous studies; however, research that specifically discusses its implications for the welfare of business actors remains limited. This study aims to analyze the forms of misuse of financing funds, their causal factors, and their implications for the welfare of MSME actors at BPRS Haji Miskin Pandai Sikek. This study employed a qualitative approach with a case study design. The research informants consisted of BPRS management and MSME actors selected through the purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation and were then analyzed using thematic analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that the misuse of financing funds predominantly takes the form of using funds for nonproductive needs, lack of openness regarding business information, and noncompliance with financing contracts. These deviations have an impact on low business growth, income stagnation, the absence of asset growth, and increased risk of default. These findings contribute to the development of agency theory and broaden understanding of customer behavior in Islamic financing. The conclusion of the study emphasizes that supervision, financial literacy, and compliance with contracts are important factors in ensuring the effective use of financing funds. The practical implication is that Islamic financial institutions need to improve their monitoring systems and business assistance so that financing can contribute more optimally to the welfare of MSME actors.